(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
درست البينة الهندسية، وتماكب الجزيء 2 – ميتيل بروبانيول كلوريد في الوضع الإلكتروني الأساسي في الحالة الغازية باستخدام طرائق Ab.initio RHF)، و DFT، و MP2، و (QCISD. عولجت سطوح الطاقة الكامنة (PES)، والمناطق الموافقة للتحولات بين المماكبات نتيجةً لدوران مجموعة الإيزوبروبيل، ومجموعتي الميتيل بتقريب أحادي البعد. درس تأثير مجموعة من التوابع المدارية الذرية الأساسية والطرائق المختلفة في دقة تحديد صفات المنحنيات (PES). وجد أن القيم المحسوبة لفرق الطاقة بين المماكبات (DE) تنسجم جيدا مع القيم التجريبية عند استخدام بعض التوابع الذرية الأساسية المقبولة. قورنت قيم الحواجز الكمونية للتحولات gauche « gauche، و cis ® gauche، وكذلك الحواجز الكمونية لدوران المجموعة الإيزوبروبيلية ومجموعتي الميتيل مع تلك القيم النظرية والتجريبية العائدة لجزيئات شبيهة، مثل 2- ميتيل بروبانول، و2 – ميتيل بروبيونيل فلوريد. The geometric structure and isomerization of the 2-methylpropionyl chloride molecule in the ground electronic state in gaseous phase was studied using Ab initio methods (RHF, DFT, MP2 and QCISD). The potential energy surface (PES) and regions corresponding to transitions between conformers by the rotation of the isopropyl and two methyl groups was examined in one-dimensional approximation. The influence of the atomic orbital basis set and the method on the accuracy of the calculation of PES characteristics was considered. The calculation of the energy differences of conformers (DE) using reasonable basis sets provides values in good agreement with experimental results. The values of the potential barriers to gauche « gauche and cis ® gauche transitions, and also the barrier of isopropyl and two methyl groups were compared with the same values for similar molecules as 2-methylpropanol and 2-methypropiony fluoride.